Hubungan Hukum antara Notaris dengan Karyawan Notaris - Juli Maria (MODELING: Jurnal Program Studi PGMI, 2017)
The development of legal relationships in society such as business relationships, land, banking, and other social relationships, which require authentic deeds as evidence to determine the rights and obligations of the parties, makes the need for the existence of Notary increasing. Along with that, the increase in the number of Notaries which in this case is ready to provide his services to create an authentic deed for members of the community in need, is also increasing. Notary not only exercises the authority and authority of public law, but Notary also performs the act of civil law (privaatrechtelijke handeling) as well as a citizen (in a personal sense) who can perform actions including in the matter of appointment to prospective employees Notary. Notary Employment Relationships with Notary Employees are established after the Working Agreement between the two parties. The Working Agreement contains the rights and obligations of the parties. The basis of the fulfillment of these rights and obligations is contained in the Manpower Act. If either party can not perform the obligation, then a legal effort may be made.